The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.21273/jashs.101.6.640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3-CPA and Ethephon on Growth and Abscission of the ‘Cardinal’ Peach1

Abstract: In central Italy neither 3-chlorophenoxy-propionamide (3-CPA) nor (2-chloroethyl)phosphonic acid (ethephon) satisfactorily thinned ‘Cardinal’, a very early peach (Prunus persica L.), when applied in the first stage of fruit growth. Both substances reduced crop load to the degree obtained by hand-thinning. 3-CPA exhibited a delayed thinning action. Ethephon was more potent and quicker than 3-CPA in inducing abscission, but at harvest time the fruit size was smaller than hand-thinned peaches. The time course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Injury increased with concen tration and number of applications. The stressed and dying tissue produce ethane in certain situations (6,11,19). Because of the importance of water stress in plants and the lack of any specific information, this study was initiated to examine the ef fects of water stress on ethylene and ethane production, using leakage meas urements to assess the point at which the stress results in cell damage.…”
Section: •Y-mentioning
confidence: 99%
See 1 more Smart Citation
“…Injury increased with concen tration and number of applications. The stressed and dying tissue produce ethane in certain situations (6,11,19). Because of the importance of water stress in plants and the lack of any specific information, this study was initiated to examine the ef fects of water stress on ethylene and ethane production, using leakage meas urements to assess the point at which the stress results in cell damage.…”
Section: •Y-mentioning
confidence: 99%
“…Severe reductions in fruit size on poorly thinned trees will occur in ex tremely dry seasons. Numerous materials have been used for chemical thinning of peaches but none have provided consist ent, acceptable results on all cultivars (2,4,5,6,7,8,9,10). Byers (3) found that the thinning response with CGA 15281 varied with cultivar, timing, concentra tion, and year.…”
mentioning
confidence: 99%
“…These cultivars were 'Cam den', 'Coronet', 'Redhaven', 'Ranger', 'Redglobe', 'Babygold 5', and ' Babygold 7'. In 1974, 1975, and 1976, single-tree plots were sprayed with a high-pressure sprayer equipped with a hand gun. From 1977 through 1981, 2-tree plots were sprayed with an air-blast power sprayer, duplicating the volume of spray de livered with hand-gun dilute applications in earlier years (7.6 liters of solution applied per tree per year).…”
Section: Methodsmentioning
confidence: 99%
“…In the early 1970s, the proprietary companies ceased production of NPA and 3CPA due to the lack of demand caused by poor performance in certain areas of the United States, even though the chemicals performed well on some cultivars in South Carolina. (2-Chloroethyl)phosphonic acid (ethephon) an ethylene-releasing ma terial, was researched for several years as a thinner for peaches in South Carolina as well as in other areas of the United States (1,5,7,8,10,11,14,17,19,20). In 1972, the proprietary company dropped its efforts to obtain clearance for peaches due to severe tree injury, particularly in the northeastern areas of the United States.…”
mentioning
confidence: 99%
“…Chemical thinning of peaches has been tested extensively but there is still no reliable and safe thinner avail able for commercial use (10). Post bloom applications of the ethylene releasing chemical, ethephon, has been known to have both under and over thinned peaches (2,4,7). However, ethephon often causes phytotoxic side effects, such as chlorosis, leaf drop, and gummosis of the fruit and wood in peach (2,4,7), and other stone fruits (1 ,5 ,9 ).…”
mentioning
confidence: 99%